2017
DOI: 10.1002/anie.201611851
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Monomeric SiO2 Complex with Donor–Acceptor Ligands

Abstract: Isolation of a monomeric SiO compound 3 as a stable donor-acceptor complex with two different ligands -a σ-donating ligand (pyridine, dimethylaminopyridine, N-heterocyclic carbene) and a donor-acceptor ligand (iminophosphorane)-is presented. The SiO complex 3 is soluble in ordinary organic solvents and is stable at room temperature in solution and in the solid state. Of particular interest, 3 remains reactive and can be used as a stable and soluble unimolecular SiO reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
39
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 63 publications
6
39
0
Order By: Relevance
“…Thep hotolysis of 2 (l = 300 nm) under CO 2 pressure (4 bars) at À50 8 8Cl eads to the formation of the mixed SiO 2 -CO 2 cycloadduct 3 stabilized by an iminophosphorane D/Aligand (Scheme 1). Similar to the previously reported SiO 2dimer VIII, [12] in 3, the silanone moiety is well stabilized by the push-pull system of the iminophosphorane ligand. Indeed, in the 29 Si NMR spectrum, the signal corresponding to the silacarbonyl function appears as ad oublet at d = À69.1 ppm ( 2 J SiP = 14.9 Hz) in the same range as that of VIII (À74.0 ppm).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Thep hotolysis of 2 (l = 300 nm) under CO 2 pressure (4 bars) at À50 8 8Cl eads to the formation of the mixed SiO 2 -CO 2 cycloadduct 3 stabilized by an iminophosphorane D/Aligand (Scheme 1). Similar to the previously reported SiO 2dimer VIII, [12] in 3, the silanone moiety is well stabilized by the push-pull system of the iminophosphorane ligand. Indeed, in the 29 Si NMR spectrum, the signal corresponding to the silacarbonyl function appears as ad oublet at d = À69.1 ppm ( 2 J SiP = 14.9 Hz) in the same range as that of VIII (À74.0 ppm).…”
supporting
confidence: 88%
“…In the same vein, we have recently reported the synthesis of SiO 2 dimer VIII stabilized by an iminophophorane-type donor-acceptor (D/A) ligand as well as the first SiO 2 molecule IX stabilized by am ixed (donor) La nd (donoracceptor) D/A ligand system. [12] Thes tability of these molecules is mainly due to the peculiar effect of the D/A ligand, which efficiently binds the silanone (> Si = O) moiety. [12,13] Here,w er eport au nique RT reversible [2+ +2] cycloaddition between as ilanone function and CO 2 ,l eading to the first persistent SiO 2 -CO 2 cycloadduct of type IV stabilized by aD/A ligand.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Furthermore,B aceiredo and Kato et al reported am onomeric SiO 2 complex using donor-acceptor interactions. [10] Herein, we report the remarkably facile access to the first isolable monomeric SiSe complexes as well as the first example of the structurally characterized monomolecular SiTe 2 species supported only by Lewis donors.…”
mentioning
confidence: 99%
“…[9] Furthermore,B aceiredo and Kato et al reported am onomeric SiO 2 complex using donor-acceptor interactions. [10] Herein, we report the remarkably facile access to the first isolable monomeric SiSe complexes as well as the first example of the structurally characterized monomolecular SiTe 2 species supported only by Lewis donors. Tr eatment of the silylone-GaCl 3 adduct 1 [7] in acetonitrile with 1/8 molar equivalents of red selenium (Se 8 )a tr oom temperature for 3h leads to ay ellow solution, from which yellow crystals of (bis-NHC)Si( = Se)GaCl 3 2 were obtained in 65 %y ield (Scheme 2).…”
mentioning
confidence: 99%